Cost of an outbreak of pleuropneumonia of swine - Protas, José Fernando da Silva; Sobestiansky, Jurij; Wentz, Ivo; Piffer, Itamar Antônio (Pesquisa Agropecuaria Brasileira, 2014)
An evaluation of the economic efficiency of a finishing pigs herd, under an acute outbreak of pleuropneumonia, which occurred at Chapecó, SC, Brazil, from May of July of 1981, was made. The mortality index of these finishing pigs changed from 100, in Junuary, to 1,627, in June. In the following months, the index dropped to 240 but never below this point. This last index may suggest the permanence of the infection in spite of drug therapy. The economic losses with death and drugs during the three months of the outbreak exceeded cruzeiros 1,852,849.59 (september 1981) the average of those registered before and after the disease. In terms of finishing pigs, this value represented a loss of 31,681 kg (21,081 kg by death and the equivalent of 10,600kg due to the cost of medication).